1991
DOI: 10.1039/c39910000634
|View full text |Cite
|
Sign up to set email alerts
|

The self-assembly of a highly ordered [2]catenane

Abstract: Template-directed synthesis has been used to construct a [2]catenane in which the two molecular components, the cyclobis(paraquat-p-phenylene) tetracation and 1,5-dinaphtho-38-crown-10, are found to be ordered non-covalently with respect to each other in both the solid (by X-ray crystallography) and solution (by NMR spectroscopy) states and to influence each other to the extent of establishing electrochemical gradients for the stepwise one electron reductions of the two paraquat units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 10 publications
(14 reference statements)
0
42
0
Order By: Relevance
“…Apolar binding is generally strongest in solvents with low molecular polarizability and with high cohesive interactions, and it has been suggested that the empirical solvent polarity parameters E T (30) for the various solvents represent a good measure of the interplay between these two factors. [22] That the driving force for the complexation of aromatic guests by the tetracation 9 4 is apolar binding would be also confirmed by a study of solvent effects on the binding equilibria between 9 4 and the guests indole and catechol. [24] The authors reported good linear free-energy relationships between the free energies of complexation and the polarity of the solvent, as measured by Z-values or E T (30) values, indicative of apolar binding complexation.…”
Section: Resultsmentioning
confidence: 81%
“…Apolar binding is generally strongest in solvents with low molecular polarizability and with high cohesive interactions, and it has been suggested that the empirical solvent polarity parameters E T (30) for the various solvents represent a good measure of the interplay between these two factors. [22] That the driving force for the complexation of aromatic guests by the tetracation 9 4 is apolar binding would be also confirmed by a study of solvent effects on the binding equilibria between 9 4 and the guests indole and catechol. [24] The authors reported good linear free-energy relationships between the free energies of complexation and the polarity of the solvent, as measured by Z-values or E T (30) values, indicative of apolar binding complexation.…”
Section: Resultsmentioning
confidence: 81%
“…1A, the relaxation process must be associated with a free energy of activation (ΔG ‡ value) of less than 16 kcal mol −1 . Both the degenerate (49,50) and nondegenerate (27) [2]catenanes (Fig. 3A), which have been studied in the dim and distant past crystallized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Macrocyclic polyethers incorporating a variety of p-electron-rich aromatic units, such as 1,5-dioxynaphthalene (DNP) [23] and resorcinol [24] ring systems, have also been shown to act successfully as templates for the formation of the tetracationic cyclophane, thus generating [2]catenanes. In addition, introduction of two different p-electron-rich aromatic residues within the same macrocyclic polyether component of a [2]catenane leads to a wide range of molecular structures [25].…”
Section: Catenane Chemistry With the Tetracationic Cyclophanementioning
confidence: 99%